The impact of human activities on water pollution in the city of Kut (Journal of the College of Basic Education, 2026)
The city of Al-Kut, located on the Tigris River in southern Iraq, has faced significant challenges in maintaining the quality of its water resources due to the increasing impact of human activities on water sources. This research aims to identify the various sources of water pollution and clarify the consequences of these sources on the environment and agricultural productivity, relying on field work to determine these sources and reveal the most significant and polluting contributors to the river's water in the study area. It was found through fieldwork that there are several sewage pipes, totaling nine, that discharge human activity waste into the river water without any treatment, leading to the accumulation and increase of toxic and dissolved substances in the river water. Laboratory test results of water samples indicated that all sample sites along the river section in the study area—comprising three sites (initial sample, middle sample, final sample)—exceeded the local and international permissible standards. The highest recorded pollutant levels were found at the final sample, attributed to it being the last station for the accumulation of pollutants. Furthermore, it was determined that the water from the Tigris River is unsuitable for drinking purposes due to the presence of coliform bacteria; however, the analyses confirmed its suitability for industrial and agricultural purposes during the research period